Characterization and Molecular Determinants for β-Lactam Specificity of the Multidrug Efflux Pump AcrD from Salmonella typhimurium - Jenifer Cuesta Bernal; Jasmin El-Delik; Stephan Göttig; Klaas M. Pos (Antibiotics, 2021)
Gram-negative Tripartite Resistance Nodulation and cell Division (RND) superfamily efflux pumps confer various functions, including multidrug and bile salt resistance, quorum-sensing, virulence and can influence the rate of mutations on the chromosome. Multidrug RND efflux systems are often characterized by a wide substrate specificity. Similarly to many other RND efflux pump systems, AcrAD-TolC confers resistance toward SDS, novobiocin and deoxycholate. In contrast to the other pumps, however, it in addition confers resistance against aminoglycosides and dianionic β-lactams, such as sulbenicillin, aztreonam and carbenicillin. Here, we could show that AcrD from Salmonella typhimurium confers resistance toward several hitherto unreported AcrD substrates such as temocillin, dicloxacillin, cefazolin and fusidic acid. In order to address the molecular determinants of the S. typhimurium AcrD substrate specificity, we conducted substitution analyses in the putative access and deep binding pockets and in the TM1/TM2 groove region. The variants were tested in E. coli ΔacrBΔacrD against β-lactams oxacillin, carbenicillin, aztreonam and temocillin. Deep binding pocket variants N136A, D276A and Y327A; access pocket variant R625A; and variants with substitutions in the groove region between TM1 and TM2 conferred a sensitive phenotype and might, therefore, be involved in anionic β-lactam export. In contrast, lower susceptibilities were observed for E. coli cells harbouring deep binding pocket variants T139A, D176A, S180A, F609A, T611A and F627A and the TM1/TM2 groove variant I337A. This study provides the first insights of side chains involved in drug binding and transport for AcrD from S. typhimurium.